A formação pedagógica de um curso de letras: as perspectivas de formadores e egressos sob um olhar complexo - Batista, Júlia Pereira (2023)
This study aims to describe and interpret two perspectives of the phenomenon pedagogical formation provided by the Language Course of a public university, as experienced by teacher educators and egresses from the same institution. The guiding questions are: (1) What is the nature of the pedagogical formation provided by the Language Course from the teacher educators’ perspective? and (2) What is the nature of this pedagogical formation from the egresses’ perspective? This study was guided by the interpretation of the curricular matrix that underlies the Pedagogical Formation Nucleus of the mentioned Language Course, articulated with what is foreseen and what has been accomplished by the course, considering the perceptions of educators and egresses. Theoretically, this study was based on the notion of complex thinking, by Morin (2005; 2013, 2015), and on studies on teacher education in the field of Applied Linguistics, mainly by Celani (2010, 2013); Freire (2017); Freire and Leffa (2013), Magalhães (2010), among others, which allowed delineating a new teaching profile: the teacher as a complex system. In methodological terms, the complex hermeneuticphenomenological approach (FREIRE, 2012; 2017) was adopted since it aims to describe and interpret phenomena of human experience. The research involved the participation of four teacher educators from the mentioned Language Course and four egress teachers who work as language teachers. A questionnaire and serial interviews were used as instruments for text generation and registration. The interpretation of these texts reveals that educators and egresses experience the phenomenon in question differently, allowing the interpretation of their perspectives as a dialogue of opposites, as detailed and commented in this thesis